Report of proceedings at the forty-fourth annual Trades union congress : held in the Town hall, Newcastle-upon-Tyne, on september 4th to 9th, 1911 - Trades union congress (44 ; 1911 ; Newcastle-on-Tyne)
Published by authority of the Congress and the Parliamentary committee